Calvin's sudden conversion (subita conversio) and its historical meaning - H. B. Lee (Acta Theologica)
In Calvin research of the Twentieth Century, different approaches towards the question about Calvin’s ‘conversion’, as mentioned in the introduction to his commentary on the Psalms, have been followed. In this article a number of these approaches are discussed, as well as certain other issues, which should be taken into account. After a discussion of these issues the conclusion is drawn that Calvin’s conversion was not the product of a gradual recognition and human decision, but an event of a decisive regeneration, resulting in true and evangelical faith under the sovereign guidance of God. Calvin’s thought on the sovereignty of God provided the guiding principle for the Reformed faith. Therefore, Calvin’s conversion was more than the conversion of an individual. It was rather a matrix for the formation of the Reformed faith and the Reformed and Presbyterian Churches. It was also the guidance and special providence of God, completing the Reformation.